P177 Outcomes of Pseudomonas Aeruginosa (PA) Eradication in Non-Cystic Fibrosis Bronchiectasis. Forced Vital Capacity (FVC) and Latent Period from Growth to Eradication Are Significant Variables in Eradication Success. (19th November 2012) - Ejiofor, S; Packer, G; Mckinley, K; Whitehouse, J
Abstract : Introduction: PA colonisation is associated with a more rapid decline in lung function and poorer health outcomes and possibly increased mortality in non cystic fibrosis bronchiectasis. 1, 2 Early aggressive antibiotic therapy is aimed at negating these deleterious effects and is recommended by the British Thoracic Society (BTS). 3 Within Heart of England NHS Trust a policy of PA eradication has existed since 2005. Method: All patients with a clinical presentation of and HRCT-confirmed bronchiectasis were identified retrospectively from a respiratory outpatient database created in 2005. Patients were included in the study if they a) cultured PA in sputum (usually 1st growth) b) underwent treatment with eradication intent and c) had at least 12 months follow up from the initiation of eradication therapy. Eradication was defined as three negative sputum samples taken following eradication treatment. Eradication regimens broadly followed the BTS guidance. Mann U Whitney and χ2 tests were used in statistical analyses. Results: see table 1 Eradication of PA was achieved in 51/72 (71%) of patients. Of those eradicated 36/51 (71%) did not reculture PA to date. Mean time in months from first growth to eradication (6.82 vs 16.19) was significantly lower in the group successfully eradicated (p<0.0001). FVC % predicted was significantly higher in the PA eradicated group (p=0.006). Conclusions: Eradication of PA can be undertaken with relatively high success rates and with almost three quarters remaining free from PA. Good lung function and a short latent time from growth to eradication are independently associated with eradication success. References: Martínez-García M A et al. Chest 2007; 132:1565–1572. Loebinger MR et al. Eur Respir J 2009 34(4) 843–849. BTS guideline for non CF bronchiectaisis Thorax July 2010 65 (1).